2005
DOI: 10.1111/j.1348-0421.2005.tb03715.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 Up‐Regulates T‐Tropic Human Immunodeficiency Virus Type 1 Transcription in Primary CD4+ CD38+ T‐Lymphocyte Subset

Abstract: The capacity of human immunodeficiency virus type 1 (HIV‐1) to infect resting cells and to produce progeny particles may contribute significantly to its pathogenicity in vivo. We previously reported that primary culture of resting CD4+ CD38+ T‐lymphocyte subset had higher production rate of CXCR4‐using (X4) HIV‐1 than CD4+ CD38− subset. Interleukin (IL)‐4 highly contributed to the up‐regulation of the X4 virus production in the CD38+ subset. Here, we show evidences that IL‐4 treatment of both resting CD38+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…To identify the factors present in conditioned medium necessary to render tissue-derived naive CD4 T cells permissive, we considered the study by Unutmaz et al ( 18 ), which showed that 10–20 ng/ml IL-2, -4, -7, or -15 rendered otherwise unstimulated blood-derived CD4 T cells susceptible to HIV infection. Consistent with this and other studies ( 19 , 20 ), we found that addition of 20 ng/ml IL-2, -4, -7, or -15 was sufficient for tissue-derived naive CD4 T cells to sustain a spreading infection (unpublished data).…”
Section: Resultssupporting
confidence: 91%
“…To identify the factors present in conditioned medium necessary to render tissue-derived naive CD4 T cells permissive, we considered the study by Unutmaz et al ( 18 ), which showed that 10–20 ng/ml IL-2, -4, -7, or -15 rendered otherwise unstimulated blood-derived CD4 T cells susceptible to HIV infection. Consistent with this and other studies ( 19 , 20 ), we found that addition of 20 ng/ml IL-2, -4, -7, or -15 was sufficient for tissue-derived naive CD4 T cells to sustain a spreading infection (unpublished data).…”
Section: Resultssupporting
confidence: 91%
“…In our preliminary testing, we confirmed the findings presented in prior reports (49,50,81,83) that exposure of resting peripheral blood CD4 ϩ T cells to IL-2, IL-4, IL-7, or IL-15 enhances infection without inducing T cell activation. Prior studies have demonstrated that cytokines have multiple influences on resting T cells that increase the permissiveness of these cells to HIV-1 replication.…”
Section: Resultssupporting
confidence: 90%
“…S5 in the supplemental material), the viruses expressed HIV-1 envelope protein from the native virally encoded env gene. ϩ resting T cells (82,83), and in tonsils, IL-4 has been shown to increase the permissiveness of resident CD4…”
Section: Resultsmentioning
confidence: 99%
“…In turn, TNF‐α supports IFN‐γ expression and may promote CD4 depletion [10]. A role for Th2 cytokines on HIV‐1 activity is more controversial [11,12]. Transforming growth factor (TGF)‐β, a prominent anti‐inflammatory cytokine is abundant during TB and may promote viral activity by counteraction to anti‐HIV‐1 immune responses either directly or through support of expansion of regulatory T cells (T reg ) [13,14].…”
Section: Introductionmentioning
confidence: 99%